Microsoft Visual C++5.0 programmer's reference set : (Microsoft Press, 1997)
This is three books in one volume: "The C Language Reference, The C++ Language Reference", and "The Preprocessor Reference", a technical reference for C and C++ programmers that documents preprocessor commands, macros, and error messages. This is the complete, from-the-source programmer's reference to Microsoft Visual C++.